Pengaruh Media Sosial, Promosi, Dan Persepsi Konsumen Terhadap Tingkat Kunjungan Funworld Di Grand Mall Batam - Zalukhu, Asipentitanis; Oktavia, Yunisa (SEIKO : Journal of Management & Business, 2023)
In this study, there are problems that affect the level of visits, namely the social media used does not provide complete information, the promotions offered are still not optimal, consumer perceptions get bad experiences when visiting which causes the level of visits to decrease. This study aims to determine the influence of social media, promotion and consumer perception on the level of Funworld visits at Grand Mall Batam, both persial and simultaneously. The population in this study was 100 respondents. Researchers use non-probability sampling techniques as techniques used to conduct this research, collecting data in the form of questionnaires and using Likert scales. Data processing using SPSS program version 25. The results of this study showed that the social media variable (X1) obtained a calculated t value of 2.114 > t Table 1.984 and significant 0.037 < 0.05, variable (X2) obtained t Calculate 0.826 > t Table 1.984 and significant 0.411 < 0.05, variable (X3) t Calculate 6.545 > t Table 1.984 and significant 0.000 < 0.05. Social media, promotions, and consumer perceptions have a significant effect on the level of visits shown from the value of F count 79.107 > 2.70 F Table and sig 0.000 < 0.05. The R value of 2 is 0.712 which means only 0.712% of the influence of Social Media, Promotions, and Consumer Perceptions on Funworld Visit Rate and the rest is influenced by variables that are not in this study. Keywords: Social media; Promotion; Consumer perception; and Visit rate.